PENGARUH RETURN ON ASSETS (ROA), CASH FLOW, DAN LIKUIDITAS TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERCATAT PADA BEI (BURSA EFEK INDONESIA) PERIODE 2016 - 2020 - MARDIAH HASANAH NASUTION (JURNAL ILMIAH SIMANTEK, 2021)
The purpose of this study is to know effect return on assets, cash flow, and liquidity to dividend payout ratio at companysector industry base and chemistry. This type of research is used descriptive quantitative research. Population in theresearch is the company sector industry base and chemistry in Indonesian Stock Exchange in the period 2013-2014 and get15 samples company the selected be base on criteria certain agree with purpose research. This method of research is usedmultiply regression analysis. The result showed that return on asset and cash flow has no influence. And liquidity asinfluence. And in a partial variable return on assets, cash flow andliquidity has influence significant to dividend payout ratio.The third variable in a simulation influence variable dividend payout ratio amounted 33,9% and meanwhile amounted 66,1%are influenced by other variable has no used in the research.